(untitled) (Journal of history, 2019)
The article analyses religious confessional politics of Russian royalty related to Turkic Muslim people. Russian royalty pursues its own interest in order to invade Turkic Muslim people. Religious politics of royal’s monarchy composed of several stages. Establishing Orynbor Muftiate led to rigid control over Islam and religious leaders. Permission was given by royal to build mosques and religious schools for Turkic-Muslim countries, and it was allowed for Tatar mullahs to come to Kazakh land by law. However, royal government who was afraid of facing religious Muslimfanatics banned religion and persecuted religious Muslims. It was clear that royal’s politics related to Turkic Muslims, following traditional Islam for many centuries, aimed at uniting and strengthening and maintaining their religion.